Stress Relaxation Behaviour and Model of Multi-Layered Nano-Hydroxyapatite Reinforced PVA Gel Biocomposites - Pan, Yusong; Xu, Chuyang; Ding, Guoxin (Asian Journal of Chemistry, 2012)
Stress relaxation characteristics of multi-layered graded nano-hydroxyapatite/PVA gel biomaterial under different effect factors were studied. The results showed that the stress relaxation behaviour of the biocomposites is similar to that of natural articular cartilage and it can be described by logarithmic model. The stress relaxation rate declined with the rise of relaxation time, but it increases with the rise of compressive strain level and freeze-thaw cycle times under the whole relaxation time. Moreover, the normalized equilibrium relaxation modulus of the composites decreases with the rise of strain and freeze-thaw cycle times.